2021
DOI: 10.3390/s21124069
|View full text |Cite
|
Sign up to set email alerts
|

ZnO@ZIF-8 Core-Shell Structure Gas Sensors with Excellent Selectivity to H2

Abstract: As the energy crisis becomes worse, hydrogen as a clean energy source is more and more widely used in industrial production and people’s daily life. However, there are hidden dangers in hydrogen storage and transportation, because of its flammable and explosive features. Gas detection is the key to solving this problem. High quality sensors with more practical and commercial value must be able to accurately detect target gases in the environment. Emerging porous metal-organic framework (MOF) materials can effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…The XRD results are shown in Figure 2 d to characterize the phase structure of the samples. It can clearly be seen that the XRD patterns of ZnO and ZIF-8 were consistent with the standard cards [ 42 ], indicating a successful synthesis of the samples. After the carbonization of ZIF-8, the disappearance of the ZIF-8 peaks in the C–ZnO samples suggest a destroyed crystal structure of ZIF-8.…”
Section: Resultssupporting
confidence: 58%
“…The XRD results are shown in Figure 2 d to characterize the phase structure of the samples. It can clearly be seen that the XRD patterns of ZnO and ZIF-8 were consistent with the standard cards [ 42 ], indicating a successful synthesis of the samples. After the carbonization of ZIF-8, the disappearance of the ZIF-8 peaks in the C–ZnO samples suggest a destroyed crystal structure of ZIF-8.…”
Section: Resultssupporting
confidence: 58%
“…Metal organic frameworks (MOFs), as typical coordination polymers developing rapidly in recent years, exhibit plenty of advantages when used in CO or CO 2 gas sensors, such as special three-dimensional structure, high porosity, low density, large specific surface area, etc. , MOFs with unique gas adsorption and separation characteristics can be utilized as a high-performance membrane-sensing material. The limitation effect of MOF membrane can selectively adsorb some gas molecules with small kinetic diameter (e.g., CO or CO 2 ) to thus improve the selectivity of the prepared gas sensors.…”
Section: Gas-sensing Optimization Strategies Used For Various Thermal...mentioning
confidence: 99%
“…22,23 For example, it has been reported that the ZIF-8 shell leads to a better selectivity to H 2 and a decreasing response toward ethanol and acetone. 19 The combination of ZnO and ZIF-8 for sensing applications has been thoroughly investigated, and a summary of the results is given in Table S1. 8,16,17,19,20,24−27 Important performance parameters are the operation temperature, morphology, and particle size of ZnO, the coating thickness of ZIF-8, and the architecture of the composite, which mutually influence each other.…”
Section: ■ Introductionmentioning
confidence: 99%
“…18 However, almost all the developed sensors shown in Table S1 respond also to other gases such as CH 4 , CO, and other hydrocarbons, which makes them unsuitable for applications in gas mixtures. Comparing the results of the studies using ZnO nanoparticles 19 with that on micro-and nanorods, 8,[16][17][18]20 it can be assumed that ZnO− MOF−ZnO conjunctions hinder the conductivity of the ZnO semiconductor because the MOF acts as an insulator. Further improvement of the performance could be possible by using single-crystalline low-defect ZnO microrods or tetrapods, adjustment of the layer thickness, and the prevention of textural porosity of the ZIF-8 layer by uneven coating or microcracks.…”
Section: ■ Introductionmentioning
confidence: 99%